Prototipe Sistem Monitoring Pemakaian Air PDAM untuk Rumah Tangga Berbasis Aplikasi Android - Anisa Eka Fajriaty; Prasetyo Yuliantoro; Muntaqo Alfin Amanaf; Nur Afifah Zen (Science Tech: Jurnal Ilmu Pengetahuan dan Teknologi, 2022)
Water is one of the most important elements in household life. Most households use PDAM services to meet their daily water needs. The use of water used for households is monitored by officers manually. This method causes various problems, namely errors in the recording by officers, errors in the process of input results, and ineffectiveness. One solution to overcome these problems is to design a monitoring system for PDAM water usage in real time. The design is made using NodeMCU as a microcontroller, Water Flow Sensor, RTC DS3231, 20X4 LCD, MIT App Inventor, and Firebase which will be displayed via LCD and Android application. The results showed that the designed tool can display data in the form of time, the volume of water, and cost with sensor accuracy of 98, 40%. In addition to these data, this study also produces QoS values, namely 0% packet loss, and 0,09 s delay.